Reminders can enhance or impair episodic memory updating: a memory-for-change perspective. Issue 6 (3rd July 2019) - Wahlheim, Christopher N.; Smith, Wyatt G.; Delaney, Peter F.
ABSTRACT: The Memory-for-Change framework proposes that retrieving episodic memories can facilitate new learning when changes between existing memories and new information are integrated during encoding and later recollected. Four experiments examined whether reminders could improve memory updating and enhance new learning. Participants studied two study lists of word pairs and were given a cued recall test on responses from both lists. Reminders of List 1 words pairs (A-B) appeared immediately before List 2 words pairs that included repeated cues and changed responses (A-D). Across experiments, we varied the types of reminders to determine whether differences in their effectiveness as retrieval cues would influence memory for the list membership of responses. We found that presenting intact reminders (cue-response) enhanced the memory benefits associated with recollection-based retrieval of changes relative to when no reminders appeared and when partial reminders (cue-only) appeared with and without feedback. Importantly, cue-response reminders benefitted memory when they were recognised in List 2 and when changes were later recollected. This suggests that integrative encoding can be facilitated when substantial environmental support is available to cue retrieval of existing memories. These findings have practical implications for understanding which reminders best aid the correction of memories for inaccurate information.